Technology application and up-scaling for sustaining natural resources and augmenting farm income: Farmers led market linked approach - Kaur, Prabhjot; Kumar, Pankaj; Singh, Jagwinder (Indian Farming, 2022)
Beekeeping, Low tunnel cultivation, Mushroom cultivation